(untitled) (Baltic Journal of Sport and Health Sciences, 2025)
Background and objectives: Cheating is defined as the voluntary violation of established rules, characterized by an element of deception (Green, 2006). The opposite of cheating is clean sport (Petróczi et al., 2021). A recent study revealed that up to 57.1 % athletes are using doping (Ulrich et al., 2018). Cheating in sports is associated with various factors (internal and external), but a particularly important yet less studied internal factor is values. Based on Schwartz’s (1992) theory of personal values, four higher-level value dimensions are identified: self-enhancement, self-transcendence, openness to change, and conservation. However, athletes’ intentions and behavior can be influenced not only by personal values, but also by sports values. Lee et al. (2000) identified such sports values as morality, competence and status. Depending on which values are more important to athletes, they may be inclined to behave one way or another, for example, to cheat in sports or to compete clean. Purpose of the research is to reveal the role of values in athletes’ intentions to compete clean or to cheat in sport. Methods: Two research methods were used in the dissertation: quantitative and qualitative. This methodological approach was chosen because cheating in sports is a multifaceted problem, which cannot be adequately understood using just one research method. Results: The results of quantitative research revealed that athletes are not inclined to use doping and are more likely to compete clean in sport. The most important personal value for athletes is self-transcendence. For athletes, the most important sports values relate to competence, and the least important relate to status. The personal values of self-enhancement and openness to change, and sports’ status values are positively related with intentions to use doping and negatively related with intentions to compete clean. The personal values of self-transcendence and conservation, together with the moral and competence values of sports, are negatively related with intentions to use doping and positively related with intentions to compete clean. We found a statistically significant positive relationship between doping self-regulatory efficacy and intentions to compete clean, and a negative relationship between doping self-regulatory efficacy and intentions to use doping. Statistically significant correlations were found between athletes’ attitudes towards doping and both intentions to compete clean and intentions to use doping. We found a statistically significant positive relationship between moral identity and intentions to compete clean and a negative relationship between moral identity and intentions to use doping. There is a statistically significant correlation between acceptance of cheating and acceptance of gamesmanship with intentions to use doping and intentions to compete clean. Correlational analysis revealed statistically significant relationships between the empowering climate and both athletes’ intentions to compete clean and intentions to use doping. Hierarchical regression analysis was performed in order to reveal the relationship between athletes’ internal and external factors and intentions to compete clean or intentions to use doping. Results of the qualitative research revealed two meta-themes (cheating in sports and clean sport). Additionally, themes, sub-themes and mini-themes were formed. Thematic maps were created to describe the qualitative research data. Conclusions: Cheating is related to various factors, both internal – such as personal and sports values, doping self-regulatory efficacy, moral identity, attitudes towards doping, intentions to cheat – and external – such as the empowering and disempowering climate created by a coach. When assessing the impact of internal and external factors on athletes’ intentions to cheat and compete clean, it was found that personal and sports values, moral identity, doping self-regulatory efficacy, attitudes towards doping and the coach-created climate – all these factors influence athletes’ intentions to compete clean or to use doping. Significant predictive factors for intentions to use doping were lower moral identity, lower doping self-regulatory efficacy, and positive attitudes towards doping/cheating (higher acceptance of cheating). Significant predictive factors for intentions to compete clean were more important self-transcendence, conservatism, and moral values, higher moral identity, higher doping self-regulatory efficacy and negative attitudes towards cheating (less acceptance of cheating). This means that internal factors have a greater impact on athletes’ intention to cheat compared to external factors. These are new and significant results that reveal the importance of internal factors in cheating in sports, with particular emphasis on the role of values. This is important for the development of new strategies aimed at combating cheating in sports. The qualitative study revealed how athletes and coaches perceive the factors that encourage clean sport. It was found that doping prevention initiatives should be carried out by the state, schools, sports organizations and anti-doping agencies. Since athletes become familiar with the concepts of doping at a very young age, it is believed that prevention should take place while still in school. Anti-doping policy should put more emphasis on clean sport, emphasizing the role of values, thus aiming to reduce the prevalence of doping in sports.